2019
DOI: 10.1002/jcp.28579
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine reduces the consequences of nitric oxide inhibition in pregnant rats

Abstract: Pre-eclampsia (PE) is closely associated with perinatal morbidity and mortality and we want to investigate tetramethylpyrazine (TMP)'s effects on PE. Pregnant Sprague-Dawley rats were randomly divided into five groups: normal pregnant (PC), PE, PE+TMP 20 mg/kg, PE+TMP 40 mg/kg, and PE+TMP 60 mg/kg group. The PE rat model was established via L-NAME treatment. Systolic blood pressures (SBP) and urinary protein concentration were detected via the tail-cuff method and CBB kit, respectively. mRNA levels of key gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…PE has negative consequences on maternal and fetal health during pregnancy, including increased perinatal mortality, preterm births, infants who are considered small for gestational age, high rates of cesarean deliveries, and other adverse outcomes, even in later postnatal periods (Antza et al 2018 ; Gu et al 2019 ). The relevant mechanism is not yet fully elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PE has negative consequences on maternal and fetal health during pregnancy, including increased perinatal mortality, preterm births, infants who are considered small for gestational age, high rates of cesarean deliveries, and other adverse outcomes, even in later postnatal periods (Antza et al 2018 ; Gu et al 2019 ). The relevant mechanism is not yet fully elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Human tissue from control and PE placenta and cell lysates from HTR-8/Svneo cells, HUVEC cells, and mouse placentas from the control, PE, and treated-PE groups were detected by Western blotting, as previously described (Gu et al 2019 ). Proteins extracted from tissue and cell samples were fractionated on sodium dodecyl sulfate‐polyacrylamide gel and electrophoresis gels and transferred to polyvinylidene fluoride membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) the LPS group (untreated); LPS + DMSO group: during PE modeling, DMSO solution (Sigma-Aldrich) was injected intraperitoneally from the 7th to 18th day of pregnancy at a dose of 60 mg/kg/day; (2) LPS + TMP group: during PE modeling, TMP injection (20 mg/mL, Wuxi No. 7 Pharmaceutical Factory, China) was injected intraperitoneally from the 7th to 18th day of pregnancy at a dose of 60 mg/kg/day (Gu et al 2019); (3) LPS + agomir-NC group: during PE modeling, lentiviral vectors containing negative control sequence of miR-16-5p agomir were injected into a rat tail vein from the 13th day to 18th day at a dose of 0.5 mg/kg/day; (4) LPS + agomir-16-5p group: during PE modeling, lentiviral vectors overexpressing miR-16-5p were injected into a rat tail vein from the 13rd day to 18th day at a dose of 0.5 mg/ kg/day; (5) agomir-NC + DMSO group: during PE modeling, the rats were injected intraperitoneally with DMSO solution at the dose of 60 mg/kg/day from the 7th to the 18th day of pregnancy, and the negative control of miR-16-5p agomir was injected into a tail vein at the dose of 0.5 mg/kg/day; (6) agomir-16-5p + DMSO group: during PE modeling, rats were injected intraperitoneally with DMSO solution from the 7th to the 18th day of pregnancy at a dose of 60 mg/ kg/day. From the 13th day to 18th day, lentiviral vectors overexpressing miR-16-5p was injected into a tail vein at a dose of 0.5 mg/kg/day; (7) agomir-16-5p + TMP group: during PE modeling, TMP solution was injected intraperitoneally at a dose of 60 mg/kg/day on the 7th to 18th days of pregnancy, and the lentiviral vectors overexpressing miR-16-5p was injected at a dose of 0.5 mg/kg/day through a tail vein from the 13th day to 18th day.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…A prior study has suggested that TMP injections led to remarkable therapeutic effects on pregnancy-induced hypertension through repressing fibrinolysis and enhancing microcirculation (Wang & Zhao 2003). Moreover, TMP administration attenuates placental endoplasmic reticulum stress in PE rats (Gu et al 2019). However, the molecular mechanisms underlying the pharmacological actions of TMP remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%